2020
DOI: 10.1021/acs.jmedchem.0c01394
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Characterization of Benzimidazole Derivatives as Positron Emission Tomography Imaging Ligands for Metabotropic Glutamate Receptor 2

Abstract: Three benzimidazole derivatives (13–15) have been synthetized as potential positron emission tomography (PET) imaging ligands for mGluR2 in the brain. Of these compounds, 13 exhibits potent binding affinity (IC50 = 7.6 ± 0.9 nM), positive allosteric modulator (PAM) activity (EC50 = 51.2 nM), and excellent selectivity against other mGluR subtypes (>100-fold). [11C]13 was synthesized via O-[11C]­methylation of its phenol precursor 25 with [11C]­methyl iodide. The achieved radiochemical yield was 20 ± 2% (n = 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(55 citation statements)
references
References 70 publications
2
53
0
Order By: Relevance
“…Compounds 8-13 were characterized for their functional affinity as mGluR2 PAMs and their binding selectivity against mGluR1-6 and 8 following our previous methods. 32,34 As shown in Figures 2a-c and Table 1, compound 8 showed an enhanced PAM activity than that of compound 6 in our cAMP biosensor assay (EC50, 20 nM versus 166 nM). By screening its mGluR2/3 agonist activity, compound 8 was also found to have a more potent mGluR2 agonist activity (IC50 = 136 nM) but a similar mGluR3 agonist activity (IC50 = 3 µM) than compound 6 (mGluR2, IC50 = 2 µM; mGluR3, IC50 = 9 µM).…”
Section: [Scheme 1]mentioning
confidence: 75%
“…Compounds 8-13 were characterized for their functional affinity as mGluR2 PAMs and their binding selectivity against mGluR1-6 and 8 following our previous methods. 32,34 As shown in Figures 2a-c and Table 1, compound 8 showed an enhanced PAM activity than that of compound 6 in our cAMP biosensor assay (EC50, 20 nM versus 166 nM). By screening its mGluR2/3 agonist activity, compound 8 was also found to have a more potent mGluR2 agonist activity (IC50 = 136 nM) but a similar mGluR3 agonist activity (IC50 = 3 µM) than compound 6 (mGluR2, IC50 = 2 µM; mGluR3, IC50 = 9 µM).…”
Section: [Scheme 1]mentioning
confidence: 75%
“…In vivo characterization of [ 11 C]mG2P001 as a reversible and specific PET radioligand for mGluR2 was described in our previous report. 19 Herein, the selfblocking effect using a pretreatment with unlabeled mG2P001 was investigated. As Fig.…”
Section: Resultsmentioning
confidence: 99%
“…22 Our previous studies have confirmed [ 11 C]mG2P001 as a suitable ligand to characterize mGluR2 in rat brain. 19 Herein, we demonstrated the unique feature of mG2P001-induced positive allosteric modulation in affecting the brain uptake of [ 11 C]mG2P001, where a significant radioactivity enhancement was observed in rats. This functional effect was then investigated in mGluR2expressing CHO cells with [ 3 H]mG2P001 considering the binding cooperativity of glutamate and the presence of unlabeled mG2P001.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations